Enhancement of surfactant biodegradation with an anaerobic membrane bioreactor by introducing microaeration. (October 2018) - Cheng, Zhenmin; Wei, Yuansong; Zhang, Qingqing; Zhang, Junya; Lu, Tiedong; Pei, Yuanmei
Abstract: In controlled ecological life support system (CELSS), 100% water recycle efficiency is needed. Both water and nutrients in wastewater needs reclaiming. In an anaerobic membrane bioreactor (AnMBR) designed to hydrolyze organic matters and convert organic nitrogen, accumulation of anionic surfactants and organic compounds was observed in the supernatant. To solve the problem, microaeration which had rarely been reported to enhance surfactants biodegradation in anaerobic process was introduced and it was proved to be an effective approach that resulted in concentrations of surfactants and soluble chemical oxygen demand (SCOD) in the supernatant decreasing from 9000 mg/L and 40000 mg/L to 2000 mg/L and 10000 mg/L, respectively. And the degradations followed the kinetic characteristics of zero order reaction with R 2 values of 0.9472 and 0.949. Three-dimensional excitation emission matrix (3D-EEM) analysis revealed that some activities of microbes were activated and enhanced by microaeration, which resulted in the disintegration of aggregates of large molecules, indicated by the size exclusion chromatography (SEC). After the introduction of microaeration, the emerging genera Aquamicrobium, Flaviflexus, Pseudomonas and Thiopseudomonas in the microbial community might be responsible for the effective biodegradation of the surfactants. Highlights: Microaeration effectively enhanced biodegradation of anionic surfactants. The swift degradation followed the kinetic characteristics of zero order reaction. The biodegradation processes were clearly illustrated by 3D-EEM and SEC results. Specific genera of bacteria involving with biodegradation processes were found.